2023
DOI: 10.1021/acsapm.3c01939
|View full text |Cite
|
Sign up to set email alerts
|

Ionic-Liquid-Based Aqueous Two-Phase Interfacial Polymerization of Covalent Organic Framework Membranes for Molecular Separation

Liping Liang,
Yuanqi Wang,
Weirong Ren
et al.

Abstract: Ionic liquid (IL)-based aqueous two-phase systems (ATPSs) are formed by the phase separation of aqueous mixture of ILs. Owing to their unique interfacial properties and stable interfacial zone, IL-based ATPSs can work as a promising confined space for membrane processing. Herein, for the first time, we proposed the thermoresponsive IL-based ATPSs as a platform for synthesizing covalent organic framework (COF) membranes. Upon the formation of aqueous biphasic interface at a corresponding temperature, the monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…[1][2][3][4][5][6] It has been observed that crystallization via particle attachment is prevalent across various materials, rendering the classical nucleation and growth theory inapplicable. [7][8][9][10][11] An example is the two-dimensional covalent organic frameworks (2D COFs), which have attracted significant attention in recent years owing to their promising applications in catalysis, [12][13][14][15][16] optoelectronics, [17][18][19][20][21][22][23] energy storage devices, [24][25][26][27][28] and molecular separation [29][30][31][32][33] . The properties of these materials are closely tied to the quality of their crystals, underscoring the necessity for facile synthesis of high-quality 2D COFs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been observed that crystallization via particle attachment is prevalent across various materials, rendering the classical nucleation and growth theory inapplicable. [7][8][9][10][11] An example is the two-dimensional covalent organic frameworks (2D COFs), which have attracted significant attention in recent years owing to their promising applications in catalysis, [12][13][14][15][16] optoelectronics, [17][18][19][20][21][22][23] energy storage devices, [24][25][26][27][28] and molecular separation [29][30][31][32][33] . The properties of these materials are closely tied to the quality of their crystals, underscoring the necessity for facile synthesis of high-quality 2D COFs.…”
Section: Introductionmentioning
confidence: 99%